Invasion of Endophytic Bacteria by Using Microencapsulation Technology as Stimulant in Cocoa Plants (Theobroma cacao L) - Prayoga, Gusti Yanda; Warsito, Kabul; Amrul, Hanifah Mutia Z.N. (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Fertilization is an important process in the growth of cocoa (Theobroma cacao L). Fertilizing cocoa usually used inorganic fertilizers. Using of inorganic fertilizers continuously could degrading soil fertility. One of the efforts to replace inorganic fertilizers was using endophytic bacteria as biofertilizers. Some endophytic bacteria are abundant in healthy plant tissues. The aim of this research was to obtain endophytic auxin-producing bacteria in cocoa plants and determine the effect of seed immersion and microcapsules addition of endophytic bacteria on cocoa plant growth. The research design used was Complete Randomized Design (CRD), 16 treatments and 3 replications. The first factor was immersion of cocoa seed using endophytic bacteria suspension consisting of S0= 0 hours; S1= 5 hours; S2= 6 hours and S3= 7 hours and the second factor was microcapsules addition consisting of B0= 0 gr; B1= 5 gr; B2= 10 gr; B3= 15 gr. Isolation from the roots and stems of cocoa obtained 5 isolates endophyte bacteria. Auxin assays showed that five isolates were able to produce auxin. Observations on plant height showed the best treatment was treatment B1 (32.49 cm). Observation of total leaves showed S3 treatment was the highest data (11.83 strands). Observation rod diameter parameter, highest data was S3 treatment (4.01 mm). For leaf area parameter, highest value was B1 treatment (66.64 cm2). For wet weight parameter, highest data was S3 treatment (18.41 g). Root length parameter, highest data was B3 treatment (15.78 cm).Â  Test results showed that the application of suspension and microcapsules of endophytic bacteria significantly increased growth of cocoa.